Rethinking class size. A question and answer session with Peter Blatchford about a new book and approach to the class size issue. Issue 4 (19th May 2021) - Blatchford, Peter
ABSTRACT: The issue of class size is a complex and contested topic that has divided opinion for many years. Whilst many teachers believe that smaller class sizes assist in enhancing outcomes, a number of policy influencers, policy makers and researchers argue that it has little influence on success in learning and that decreasing class sizes is not cost-effective. This article reports on over 20 years of research on this topic that is embodied in a recent text entitled Rethinking Class Size: The Complex Story of Impact on Teaching and Learning by Peter Blatchford and Anthony Russell of the University College London Institute of Education. The book offers an extended exploration of how class size affects key classroom processes including teaching, classroom management, peer relations, groups in the class, marking and other administrative teacher activities, as well effects on teachers themselves. The article is based on a question and answer session between one of the authors of the text, Professor Peter Blatchford, and his colleague at the UCL Institute of Education, Matt Somerville.